2019
DOI: 10.1007/s12034-019-1805-5
|View full text |Cite
|
Sign up to set email alerts
|

Linkage modification of a zinc oxide photoelectrode prepared with polyethylene glycol for electron transport improvement in dye-sensitized solar cells

Abstract: The purpose of this study is to synthesize ZnO aggregate films using simple precipitation with polymer modification for linkage improvement of the ZnO photoelectrode. The starting materials of zinc acetate solution and ammonia solution were mixed under violent stirring conditions. A portion of the polymer (polyethylene glycol) was slowly added into the mixed solution to obtain the viscous ZnO precursor. The precursor was then coated onto a fluorine-doped tin oxide substrate and annealed to form ZnO films. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For analyzing antibacterial performance, bacterial activities of X. campestris, P. aeruginosa, and P. fluorescens were monitored from the optical density at 600 nm [29]. Then, the antibacterial performance was evaluated in term of inhibition rate, calculated from the Equation (6) [7];…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For analyzing antibacterial performance, bacterial activities of X. campestris, P. aeruginosa, and P. fluorescens were monitored from the optical density at 600 nm [29]. Then, the antibacterial performance was evaluated in term of inhibition rate, calculated from the Equation (6) [7];…”
Section: Resultsmentioning
confidence: 99%
“…ZnO-based antibacterial performance has been demonstrated in varieties of bacteria that cause disease in plants, animals, and humans. For examples, the inhibition rates of Bacillus thuringiensis israelensis (Bti) and Escherichia coli (E. coli) were investigated using ZnO tetrapods [7]. It was found that the inhibition rates increased as a function of ZnO tetrapod concentration, and both strains were completely inhibited at the concentration of 0.75 mg•ml -1 [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD results exhibit similar diffraction patterns for all samples, which corresponds to the hexagonal wurtzite structure of ZnO, in agreement with the standard JCPDS card no. 36-1451[11]. To investigate the influence of yttrium content on the crystallization of Y-doped ZnO, the crystal characteristics including crystalline size (D), lattice constant (a and c), and d-spacing (d) were calculated according to Eqs.…”
mentioning
confidence: 99%